Content Monetisation in the Digital Age: A Maqāṣid Sharī'ah Study of Youtube, Tiktok, and Facebook Revenues - Arisman, Arisman; Rahman, Rahman (IAIN Ponorogo, 2025)
The development of digital technology has led to the practice of content monetisation on social media such as YouTube, TikTok, and Facebook, which has become a new source of income for individuals. From the perspective of maqāṣid sharī'ah, according to Abdul Majid al-Najjar, this phenomenon can be considered valid if it is in line with the five main principles, namely protecting religion (ḥifẓ al-dīn), soul (ḥifẓ al-nafs), intellect (ḥifẓ al-'aql), offspring (ḥifẓ al-nasl), and property (ḥifẓ al-māl). This research uses a qualitative-descriptive analytical approach by examining the social media accounts of Indonesian digital creators such as Atta Halilintar, Ria Ricis, and Jerome Polin and strengthening the findings with fiqh literature, fatwas of scholars, and digital economy regulations. The analysis shows that content monetisation is sharia-compliant if the content produced does not violate religious teachings (ḥifẓ al-dīn), does not feature violence or exploitation (ḥifẓ al-nafs), encourages education and the use of reason (ḥifẓ al-'aql), maintains norms of decency and family honour (ḥifẓ al-nasl), and obtains halal, transparent, and free from elements of gharar, usury, and maisir (ḥifẓ al-māl). Thus, content monetisation is acceptable within the framework of maqāṣid sharī'ah as long as it meets the established ethical and legal criteria.